THE TOPICALITY OF EDUCATORS’ DIGITAL COMPETENCE DEVELOPMENT - Spridzans, Martins; Dzerviniks, Jānis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Information and communication technologies (ICT) rapidly continue advancement in educational contexts. The influence of ICT, variety of digital learning materials and opportunities has enlarged especially in the last decade followed by the topicality of educators’ digital competence improvement. One of the key competences of educators to harness the potential of digital learning sphere is continuous development of digital competence. Authors of this research explore scientific literature on the formation, further development and assessment of teachers’ digital competence. Based on research findings the authors indicate facts that due to the lack of digital competence the potential of digital learning is not fully used, educators need to update competence on development of interactive training materials, assessment of digital competence should be more reliable and rigorous. On the basis of the research the authors put forward suggestions on the ways to develop educators’ digital competence.